RESEPSI PENGALUNGAN JIMAT KALUNG BENANG PADA BAYI DALAM TRADISI MASYARAKAT LAMONGAN - HIdayatus Sya'dyya, Dini Tri (Living Islam: Journal of Islamic Discourses, 2022)
Religious life that practiced and understood by each community is diverse. It implicates that the understanding of something good to do and what is not to do are still varies one with another. So that belief in sacred goods is still even practiced today. As for trust in sacred objects, there are still pros and cons to society, on the other hand, trust has been slightly eroded due to the rapid development of technology that is consumed by the community. However, there are also some areas that still believe in sacred objects, such as in the Lamongan area, there is a belief in necklace thread talismans worn by babies who are still developing today, so this behavior is feared to violate the Qur'an and Hadith.Keywords: Talisman Charm, Thread Necklace, Lamongan Community Tradition.Kehidupan beragama yang sering dipahami oleh setiap masyarakat ialah berbeda-beda, sehingga pemahaman terhadap seuatu yang baik untuk dilakukan dan tidak masih bervariasi. Sehingga kepercayaan terhadap barang barang keramat masih saja dilakukan sampai saat ini. Adapun kepercayaan terhadap benda kermat masih menjadi pro dan kontra terhadap masyarakat, disisi lain kepercayaan sudah sedikit terkikis dikarenakan pesatnya perkembangan teknologi yang konsumi oleh masyarakat. Namun ada juga beberapa wilayah yang masih percaya dengan benda keramat, seperti diwilayah lamongan adanya kepercayaan terhadap jimat benang kalung yang dikenakan oleh bayi yang masih berkembang sampai saat ini, sehingga perilaku ini dikawatirkan menyalahi Al-Qur’an maupun Hadis.